2012
DOI: 10.5014/ajot.2012.000604
|View full text |Cite
|
Sign up to set email alerts
|

How Sensory Experiences of Children With and Without Autism Affect Family Occupations

Abstract: We used a grounded theory approach to data analysis to discover what effect, if any, children's sensory experiences have on family occupations. We chose this approach because the existing literature does not provide a theory to account for the effect of children's sensory experiences on family occupations. Parents of six children who were typically developing and six children who had autism were interviewed. We analyzed the data using open, axial, and selective coding techniques. Children's sensory experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 23 publications
7
114
0
2
Order By: Relevance
“…Even though families engage in similar occupations in time and space, the experience of engaging in these occupations differs among the individuals within families (Bagby, Dickie, & Baranek, 2012;Evans & Rodger, 2008). Based on the theoretical framework of the Value and Meaning in Occupations model (ValMO) (Persson, Erlandsson, Eklund, & Iwarsson, 2001), perceptions of daily occupations can be operationalized as occupational values divided into three dimensions: concrete value (e.g., completing a task or a newly acquired skill) symbolic value (related to gender identity, group or culture) and self-reward value (the joy and pleasure in the doing).…”
Section: Perceptions Of Value In Daily Occupationsmentioning
confidence: 99%
“…Even though families engage in similar occupations in time and space, the experience of engaging in these occupations differs among the individuals within families (Bagby, Dickie, & Baranek, 2012;Evans & Rodger, 2008). Based on the theoretical framework of the Value and Meaning in Occupations model (ValMO) (Persson, Erlandsson, Eklund, & Iwarsson, 2001), perceptions of daily occupations can be operationalized as occupational values divided into three dimensions: concrete value (e.g., completing a task or a newly acquired skill) symbolic value (related to gender identity, group or culture) and self-reward value (the joy and pleasure in the doing).…”
Section: Perceptions Of Value In Daily Occupationsmentioning
confidence: 99%
“…Increasing evidence has shown that children with autism spectrum disorder (ASD) experience challenges in these daily routines and that their sensory differences often interfere with their ability to develop skills in these important daily routines Schaaf, Toth-Cohen, Johnson, Outten, & Benevides, 2011;Stein, Polido, & Cermak, 2012;Stein, Polido, Mailloux, Coleman, & Cermak, 2011). Eating difficulties are a frequent problem for children with autism (Hubbard, Anderson, Curtin, Must, & Bandini, 2014;Kral, Eriksen, Souders, & Pinto-Martin, 2013;Marí-Bauset, Zazpe, Mari-Sanchis, Llopis-González, & Morales-Suárez-Varela, 2014;Nadon, Feldman, Dunn, & Gisel, 2011a, 2011bSchreck & Williams, 2006;Schreck, Williams, & Smith, 2004;Suarez, Nelson, & Curtis, 2014) and may weaken their physical health Lukens & Linscheid, 2008;Sharp et al, 2013), cause difficulty during family mealtimes and milieu (Bagby, Dickie, & Baranek, 2012;Schaaf et al, 2011;Suarez, Atchison, & Lagerwey, 2014), and impede participation in the educational setting (Koenig & Rudney, 2010).…”
mentioning
confidence: 99%
“…However, according to Bagby et al (2012), the parents of children with typical development (n = 6) stated that mealtimes were events with more positive meanings compared to the parents of children with ASD (n = 6). Fulkerson et al (2008) reported that families with typically developing children (n = 107) identified that the benefits of family mealtimes included conversation, togetherness, eating well, home-cooked food, and experiencing family relations.…”
Section: (American Occupational Therapy Associationmentioning
confidence: 99%
“…In addition to these core diagnostic features, it has been documented that children with ASD are more likely to exhibit sensory differences, such as overresponding or underresponding to sensory input, that negatively impact their participation in activities of daily living, community participation, and family quality of life (Bagby, Dickie, & Baranek, 2012;O'Donnell, Deitz, Kartin, Nalty, & Dawson, 2012;Tomchek & Dunn, 2007). and found a significant (p < .001) relationship between the degree of sensory processing impairments and behavior challenges, including irritability, lethargy, stereotypic behavior, hyperactivity, and inappropriate speech.…”
mentioning
confidence: 99%